Efeitos do conhecimento do performance visual em uma frequência autocontrolada na aprendizagem de uma habilidade esportiva - Wesley Rodrigo Goncalves (2006)
Information is a critical trend to motor skill learning and its nature would be important to learning improvement. Feedback would be comprehended as any kind of looped back information related to the performed movement. One of feedback types provided by an external source to a movement performer is called knowledge of performance (KP), which informs about the aspects related to the movement pattern. One way in which KP can be provided is through the video, which demonstrates to the leaner the movement performed by him or herself. Results of previous studies that investigated the role of KP are inconsistent in indicate which are the variables that plays a major role upon KP effects and how to guides the use of this source of information. A possibility is to provide visual KP in a self-controlled frequency allowing the learner to decide the moment in which he or she wants receive this information, it permits an active participation of the subject in the learning and teaching process. The aim of this study was to investigate the effect of self-controlled visual KP in the learning of a volleyball serve. Thirty male volunteers aging from eleven to thirteen years were assigned to one of three experimental groups: 1) self-controlled group, which received KP in a selfcontrolled frequency during the acquisition phase, 2) yoked group, which received KP in the same trials that their counterparts of self-controlled group, and 3) control group, which no received visual KP. The acquisition phase was constituted by two consecutive practice days, in which 80 trials of serves were performed for each participant. An immediate transfer test was applied 10 minutes after the end of acquisition and a delayed transfer test was applied 48 hours after the end of immediate transfer test. During the transfer tests, the participants performed 10 trials of the serve in a diagonal line to the target. The achieved score and the movement pattern were the dependent variables used, and were analyzed both the means of scores and the standard deviation of scores attained. The results did not confirm the effects of visual self-controlled feedback, as well as this source of information did not show itself be efficient to the learning. The discussion was focused on in the following questions: 1) the result feedback (KR) would be enough sufficient to the pattern improvement; 2) some participants would be more challenged to achieve the accuracy goal on the target than to achieve the goal of movement pattern; 3) would be visual KP an important source of information, when analyzed the motivational and informational aspects?; 4) Would be children a worst visual KP perception, when compared to the adults?; 5) children would not be able to use the self-controlled frequency and for them, the self-controlled frequency did not increase the potential of visual KP; 6) children would be overstretched of selfcontrolled situations.